Awareness and perception of physiotherapy practice among career educators in selected secondary schools in Nigeria - Samuel Olufemi Bolarinde; Temitope Victor Owoyemi; Ayodeji Ojo Obaya; Michael Nanimebila (Wolters Kluwer Medknow Publications, 2020)
Context: High school career educators educate and counsel senior students on choice of career. The pursuit of a career in physiotherapy depends largely on the information available to the students. Aims: The aim of the study is to investigate the level of awareness and perception of the physiotherapy profession among secondary school career educators. Settings and Design: The cross-sectional study recruited 49 secondary school career educators in both public and private secondary schools in Owo local government area of Ondo-state, South-western Nigeria. Subjects and Methods: A self-administered questionnaire was used to obtain information on the level of awareness and knowledge about physiotherapy. Statistical Analysis Used: Data were summarized using mean, standard deviation, frequency, and percentiles. Results: About 95.5% of school career educators are aware of physiotherapy. 77.6% are aware that physiotherapy can be studied in university, while others believe that it can be studied in polytechnic (4.1%), college of education (2.0%), and technical schools (6.1%). 51.0% knew about adequate subject combination for gaining admission to study physiotherapy, while 49.0% did not know about the adequate subject combination. The overall knowledge score of <48.0% among school career educators indicated inadequate knowledge about physiotherapy practice, treatment modalities, and specialties. Conclusions: Secondary school career educators in this study demonstrated a high level of awareness about physiotherapy. However, their knowledge about the practice of physiotherapy, treatment modalities, specialties, and employability in institutions other than government own health facilities remains inadequate. The professional body of physiotherapy should organize programs aimed at improving the knowledge of secondary school career educators about the practice of physiotherapy.